2002
DOI: 10.1074/jbc.m206530200
|View full text |Cite
|
Sign up to set email alerts
|

The Keap1 BTB/POZ Dimerization Function Is Required to Sequester Nrf2 in Cytoplasm

Abstract: Transactivation of phase II detoxification enzymes and antioxidant proteins is mediated by the Cap'NCollar transcription factor, Nrf2, which is sequestered in the cytoplasm by the actin-binding protein Keap1. Mutation of a conserved serine (S104A) within the Keap1 BTB/POZ domain disrupts Keap1 dimerization and eliminates the ability of Keap1 to sequester Nrf2 in the cytoplasm and repress Nrf2 transactivation. Disruption of endogenous Keap1 dimerization using BTB/POZ dominant negative proteins also inhibits the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
244
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 320 publications
(253 citation statements)
references
References 53 publications
8
244
0
1
Order By: Relevance
“…Keap1 has been reported to inhibit Nrf2 by binding and sequestrating Nrf2 in the cytoplasm [25] and by targeting Nrf2 to the ubiquitin 26S proteasome degradation pathway [26]. Thus inhibition of the 26S proteasome pathway by MG132 leads to accumulation of the Nrf2 protein as shown in Figures 1 and 4.…”
Section: Discussionmentioning
confidence: 93%
“…Keap1 has been reported to inhibit Nrf2 by binding and sequestrating Nrf2 in the cytoplasm [25] and by targeting Nrf2 to the ubiquitin 26S proteasome degradation pathway [26]. Thus inhibition of the 26S proteasome pathway by MG132 leads to accumulation of the Nrf2 protein as shown in Figures 1 and 4.…”
Section: Discussionmentioning
confidence: 93%
“…Inactive Nrf 2 is localized in the cytoplasm, in part or totally, as a consequence of binding to cytoskeleton-associated protein, Keap1. 31 Recently, it has also been reported that MAP kinases, including ERKs, JNKs, and p38, are implicated in phosphorylation and stabilization of Nrf2 to facilitate its nuclear translocation 32 and binding to distinct but very similar DNA elements, individually or alternatively referred to as Maf recognition element (MARE), 33 stress-response element (StRE), 29 or antioxidant-response element (ARE). 34 In addition, PI3K/Akt signaling pathway also regulates AREs activation via the nuclear translocation of Nrf2.…”
Section: Discussionmentioning
confidence: 99%
“…It is the nearest homologue of the kelch protein of Drosophila, which binds to actin (Itoh et al 1999;Zipper and Mulcahy 2002). Keap1 acts as a substrate adapter protein for the E3 ubiquitin ligase complex formed by Cul3 and Rbx1 and targets Nf-E2/Nrf2 for ubiquitination and degradation by the proteasome (McMahon et al 2004;Bryan et al 2013) (Fig.…”
Section: Structural Insights Of Keap1-nrf2 Transcription Factormentioning
confidence: 99%